Use of expanded polystyrene wastes in developing hollow block masonry units. (30th April 2020) - Ali, Youmna A.Y.; Fahmy, Ezzat H.A.; AbouZeid, Mohamed N.; Shaheen, Yoursy B.I.; Mooty, Mohamed N. Abdel
Highlights: Block density and compressive strength decreases with the increase of EPS dosage. The increase in the EPS dosage makes the failure of the blocks more gradual. Skin reinforcement does not affect the strength, it improves the failure pattern. The skin reinforcement rust and deteriorate after exposure to saline solution. The proposed EPS hollow blocks are acceptable for non-loadbearing application. Abstract: This paper presents the results of an experimental investigation aimed at developing lightweight hollow block masonry units of adequate mechanical and durability characteristics for applications in the construction industry. Five dosages of EPS crumbles were used as partial replacement of the sand in the blocks mixture, namely; 0%, 10%, 15%, 20%, and 26%. Skin reinforcement was added to some of the tested. Three types of EPS blocks were tested: 1 – plain blocks without reinforcement, 2 – blocks reinforced with welded steel wire mesh, and 3 – blocks reinforced with fiberglass mesh. The density of the developed blocks ranged between 2119 and 982 kg/m 3 and the net area compressive strength ranged between 9.5 and 1.4 MPa. The presence of EPS in the mixture greatly improved the failure pattern of all the EPS hollow blocks. The durability tests proved that EPS hollow blocks were resilient to acid and salt exposure. The weight loss and compressive strength loss of the hollow blocks due to ettringite leach decreased significantly with the addition of EPS. The presence of the skin reinforcement had minimal effect on the compressive strength, but it improved the failure pattern. The developed EPS hollow blocks are suitable for non-load bearing application of exterior and interior walls within the stated limits of ASTM and the Egyptian Standards.